Physician Communication in Injectable Opioid Agonist Treatment: Collecting Patient Ratings With the Communication Assessment Tool. Issue 6 (December 2020) - Palis, Heather; Marchand, Kirsten; Beaumont, Scott; Guh, Daphne; Harrison, Scott; MacDonald, Scott; Brissette, Suzanne; Marsh, David C.; Schechter, Martin T.; Oviedo-Joekes, Eugenia
Abstract : Objective: Patient ratings of physician communication in the setting of daily injectable opioid agonist treatment are reported. Associations between communication items and demographic, health, drug use, and treatment characteristics are explored. Methods: Participants (n = 121) were patients receiving treatment for opioid use disorder with hydromorphone (an opioid analgesic) or diacetylmorphine (medical grade heroin). Ratings of physician communication were collected using the 14-item Communication Assessment Tool. Items were dichotomized and associations were explored using univariate and multivariable logistic regression models for each of the 14 items. Results: Ratings of physician communication were lower than reported in other populations. In nearly all of the 14 multivariable models, participants with more physical health problems and with lower scores for treatment drug liking had lower odds of rating physician communication as excellent. Conclusions: In physician interactions with patients with opioid use disorder, there is a critical need to address comorbid physical health problems and account for patient medication preferences. Practice Implications: Findings reinforce the role physicians can play in communicating with patients about their comorbid conditions and about medication preferences. In the patient-physician interaction efforts to meet patients' evolving treatment needs and preferences can be made by offering patients access to all available evidence-based treatments.